Lalang (Imperata cylindrica) as a low-cost adsorbent for removal of lead ions from aqueous solutions / Haslizaidi Zakaria, Megat Ahmad Kamal Megat Hanafiah and Sa'diah Sahat - Zakaria, Haslizaidi; Megat Hanafiah, Megat Ahmad Kamal; Sahat, Sa'diah (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2006)
The removal of lead aqueous solution with agricultural waste particularly Lalang or Imperata cylindrical (IC) leaves was investigated by the batch mode method. Effect of various operating variables such as metal ion concentration, solution pH, adsorbent dose, and temperature on the removal of lead was studied. The batch experiments show that pH 4.0 - 5.0 was the best range for the adsorption of lead ions. Time-dependent experiments revealed that binding of Pb(II) ions to the adsorbent reached equilibrium in 90 min for lead concentration of 5 mg/L and 120 min for lead concentration of 20 mg/L. Adsorption of Pb(II) was found to increase with adsorbent dosage. The adsorption capacity experiment revealed that the amount of lead ions bound per gram of adsorbent was 5.89 mg g"1. It was found that the intraparticle diffusion of Pb(II) through pores in the adsorbents was not the only rate limiting step. The adsorption of Pb(II) onto IC leaf powder increases with increasing temperature indicating endothermic nature of adsorption process. Pseudo-second-order model described the adsorption kinetics better than the pseudo-first-order, Ritchie's second order and Elovich model. The studies showed that IC leaves can be used as good adsorbent materials for Pb(II) removal from aqueous solution.